Scientific Computing with MATLAB and Octave - Quarteroni, Alfio; Saleri, Fausto; Gervasio, Paola; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This textbook is an introduction to Scientific Computing, in which several numerical methods for the computer-based solution of certain classes of mathematical problems are illustrated. The authors show how to compute the zeros or the integrals of continuous functions, solve linear systems, approximate functions using polynomials and construct accurate approximations for the solution of ordinary and partial differential equations. To make the format concrete and appealing, the programming environments Matlab and Octave are adopted as faithful companions. The book contains the solutions to several problems posed in exercises and examples, often originating from important applications. At the end of each chapter, a specific section is devoted to subjects which were not addressed in the book and contains bibliographical references for a more comprehensive treatment of the material.
What can$1 (Bt be ignored -- Nonlinear equations -- Approximation of functions and data -- Numerical differentiation and integration -- Linear systems -- Eigenvalues and eigenvectors -- Ordinary differential equations -- Numerical approximation of boundary-value problems -- Solutions of the exercises.s
Keywords: Mathematics; Chemistry; Computer science; Visualization; Engineering; Mathematics; Computational Science and Engineering; Numerical and Computational Physics; Computational Intelligence; Theoretical and Computational Chemistry; Visualization